2022
DOI: 10.7554/elife.74363
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocally inhibitory circuits operating with distinct mechanisms are differently robust to perturbation and modulation

Abstract: Reciprocal inhibition is a building block in many sensory and motor circuits. We studied the features that underly robustness in reciprocally inhibitory two neuron circuits. We used the dynamic clamp to create reciprocally inhibitory circuits from pharmacologically isolated neurons of the crab stomatogastric ganglion by injecting artificial graded synaptic (ISyn) and hyperpolarization-activated inward (IH) currents. There is a continuum of mechanisms in circuits that generate antiphase oscillations, with 'rele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
5
13
0
Order By: Relevance
“…However, following identical pathological perturbations, such as a reduction of inhibition or cell type diversity, these models displayed heterogeneous circuit responses. This is in agreement with previous work showing that perturbations in degenerate, superficially similar circuits can reveal hidden variability in synaptic and intrinsic properties leading to heterogeneous responses 8 , 41 , 250 , 251 . Such modelling insights are highly relevant also for epilepsy.…”
Section: Multiscale and Population Modelling Of Degenerate Circuits A...supporting
confidence: 93%
See 1 more Smart Citation
“…However, following identical pathological perturbations, such as a reduction of inhibition or cell type diversity, these models displayed heterogeneous circuit responses. This is in agreement with previous work showing that perturbations in degenerate, superficially similar circuits can reveal hidden variability in synaptic and intrinsic properties leading to heterogeneous responses 8 , 41 , 250 , 251 . Such modelling insights are highly relevant also for epilepsy.…”
Section: Multiscale and Population Modelling Of Degenerate Circuits A...supporting
confidence: 93%
“… 7 . In contrast to redundant components, degenerate components may generate dissimilar outputs in different contexts 2 , 8 . Therefore, although degeneracy is sometimes called also ‘partial redundancy’ 9 , we follow the terminology of Edelman and Gally 1 and distinguish degeneracy from redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SWA in mammals, which can be recorded across the entire cortical surface during NREM sleep 7 , dFBN slow waves are products of an anatomically circumscribed central pattern generator that may be numerically as simple as the two-neuron swim circuit of Clione 10 . Despite their apparent simplicity, central pattern generators are notorious for the sensitivity of their dynamics to modulatory changes in biophysical parameters 34 -36 . dFBNs experience many such changes as sleep pressure builds: they steepen their current–spike frequency functions 2,3 , modulate voltage-gated and leak potassium conductances in opposite directions 6 , and receive heightened (indirect) excitatory drive from R5 neurons 37 .…”
Section: Resultsmentioning
confidence: 99%
“…13 Calcium imaging combined with neuronal manipulations revealed that, in the circuit for selecting between the Hunch and the Head Cast, inhibitory neurons (and not the projection neurons) are the target of modulation by the changes in the feeding conditions. Inhibitory neurons were shown to be the target of contextual modulation in other systems [57][58][59] . Previous work has identified reciprocal inhibition of inhibition as a motif underlying the competition between a startle-type action and an exploratory action 35 .…”
Section: Snpfr In the Interconnected Inhibitory Interneurons Mediates...mentioning
confidence: 99%